Penerapan Metode Prototyping pada Pengembangan Aplikasi “We Listen We Don’t Judge” untuk Analisis Tautan dan Pemberian Saran Otomatis Berbasis Web - Bagus Ageng Alfahri; Alfani Azhar; Legiman Samosir; Khalil Gibran (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
This research aims to design and build a web-based application calledWe Listen We Don’t Judgewhich is able to analyze links entered by users, whether from social media or other websites. The system will automatically assess the content of the link, then provide neutral and constructive suggestions or input to users. The system development uses an approachSystem Development Life Cycle(SDLC) prototyping model to obtain a system that meets user needs. The prototype is tested iteratively to obtain feedback before entering the final implementation stage. The final result of this research is an interactive information system that is able to perform link content analysis and provide suggestions with a simple and user-friendly interface.